2004
DOI: 10.1261/rna.5263904
|View full text |Cite
|
Sign up to set email alerts
|

A novel function for Sam68: Enhancement of HIV-1 RNA 3′ end processing

Abstract: Both cis elements and host cell proteins can significantly affect HIV-1 RNA processing and viral gene expression. Previously, we determined that the exon splicing silencer (ESS3) within the terminal exon of HIV-1 not only reduces use of the adjacent 3 splice site but also prevents Rev-induced export of the unspliced viral RNA to the cytoplasm. In this report, we demonstrate that loss of unspliced viral RNA export is correlated with the inhibition of 3 end processing by the ESS3. Furthermore, we find that the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 75 publications
2
36
0
Order By: Relevance
“…Another poly(A)-binding protein, the KH-domain protein Sam68, which was shown in this and previous studies to enhance CTE function at the cytoplasmic level (Coyle et al 2003), has been reported to stimulate mRNA 39 processing, resulting in increased gene expression (McLaren et al 2004). Like Nab2, the function of Sam68 is regulated by mitogen-activated protein (MAP) kinases as well as other kinases (Matter et al 2002;Coyle et al 2003).…”
Section: Discussionmentioning
confidence: 62%
“…Another poly(A)-binding protein, the KH-domain protein Sam68, which was shown in this and previous studies to enhance CTE function at the cytoplasmic level (Coyle et al 2003), has been reported to stimulate mRNA 39 processing, resulting in increased gene expression (McLaren et al 2004). Like Nab2, the function of Sam68 is regulated by mitogen-activated protein (MAP) kinases as well as other kinases (Matter et al 2002;Coyle et al 2003).…”
Section: Discussionmentioning
confidence: 62%
“…Since the simultaneous activities of these proteins are necessary for maximal stimulation of v5 inclusion, it is possible that recruitment of SRm160 and Sam68 to v5 pre-mRNA is cooperative. Another indication that Sam68 and SRm160 might have common activity are the recent reports that both factors can stimulate the 3Ј-end processing of some pre-mRNAs (24,25,27).…”
Section: Discussionmentioning
confidence: 99%
“…Effects of WT1(+KTS) at multiple levels would not be surprising, since many recent studies have highlighted links between different steps in RNA processing (for a recent review, see Huang and Steitz 2005). In addition, Sam68, which also functions to promote translation of CTE-containing RNA (Coyle et al 2003), has been reported to also effect alternative splicing, RNA stability, and polyadenylation (Matter et al 2002;McLaren et al 2004). …”
Section: Discussionmentioning
confidence: 99%